SISTEM INFORMASI GEOGRAFIS LAHAN PERTANIAN PADA KECAMATAN BANDAR KHALIFAH BERBASIS PEMETAAN - Ilka Zufria; Septiana Dewi Andriana; Muhammad Zulfikar Lubis (JISTech (Journal of Islamic Science and Technology), 2019)
Bandar Khalifah Subdistrict is one of the sub-districts in Serdang Bedagai Regency. Bandar Khalifah District has various types of agricultural land. Agricultural land in Bandar Khalifah Subdistrict has various kinds of information (non-spatial data) related to the geographical area (spatial data). But this information cannot be processed optimally. Therefore, we need a system that is able to manage spatial data and non-spatial data so that it becomes an effective and efficient information. The system that is able to overcome this problem is GIS Agricultural Land in Bandar Khalifah District. GIS Agricultural Land District Bandar Khalifah was built using ArcView GIS Version 3.3. Digitizing techniques are used to manage spatial data in graphic form. Non-spatial data is managed in tabular forms. Spatial and non-spatial data will be displayed on the system interface. The process of making an interface on the system using the Avenue script programming language. GIS Agricultural Land District of Bandar Khalifah District presents both spatial and non-spatial information about the mapping of agricultural land in Bandar Khalifah District. This system can also be used to update information that can only be accessed by the admin. The interface on the system is a modification of the appearance of the ArcView GIS software interface.